O3-S3.04 Self-administered Neisseria gonorrheae and Chlamydia trachomatis testing in the pharynx and rectum among men who have sex with men in Washington, DC. (10th July 2011) - Sexton, M; Baker, J; Perkins, R; Nakagawa, K; Jucha, B; Baker, D; Slack, R; Arora, S; Plankey, M
Abstract : Background: Recent studies have demonstrated a high prevalence of pharyngeal (P) and rectal (R) Neisseria gonorrheae (GC) and Chlamydia trachomatis (CT) infections among men who have sex with men (MSM), which is concerning given the potential for harmful sequelae and their relationship to increased HIV transmission. CDC guidelines advocate testing MSM at least annually for these infections, but surveys of medical providers suggest that adherence to these guidelines is minimal. Because providers cite limited time and staff as common reasons for not following the guidelines, we evaluated the feasibility and accuracy of performing self-administered testing for GC and CT. Methods: 286 clients who attended Whitman-Walker Clinic in Washington, DC for HIV/STI testing participated in the study. Enrolled clients had a mean age of 36±11, represented a variety of racial/ethnic backgrounds with 52.8% identifying as Caucasian, and had an average of two male partners in the last 30 days. Clients performed screening using the GenProbe APTIMA 2 Combo (AC2) kit after viewing written and pictorial instructions. A trained provider also performed the testing with the order of client vs provider randomised to adjust for any training effect. This provider remained in the room while the client performed screening to observe, but did not provide assistance. Results: The overall prevalence of GC and CT in this sample was 8.9% for P-GC, 8.5% for R-GC, 1.77% for P- CT, and 13.3% for R-CT. McNemar tests were performed stratified by type of infection and anatomic site to evaluate concordance of the client vs provider results. Clients were found to be significantly better at identifying P-GC (91.3% vs 94.4%; 8.8% vs 5.6%; p=0.01) and R-GC (91.5% vs 94.3%; 8.5% vs 5.7%; p=0.03) and to have results equivalent to providers for P-CT (98.3% vs 98.9%; 1.8% vs 1.1%; p=0.50) and R-CT (88.7% vs 88.2%; 13.3% vs 11.9%, p=0.25) detection. Conclusions: The positive predictive value of the AC2 test makes it unlikely that clients obtained false positives, and observation of subjects while they performed screening ruled out cross-contamination of samples. Therefore, the higher detection rate among the clients is most likely attributable to a more rigorous swabbing technique that sampled an increased surface area. These results suggest that individuals are capable of performing their own STI screening and that allowing them to do so may increase infection detection rates and treatment.